¡La verdad no es como la pintan! Secuencia didáctica para promover el desarrollo de la lectura crítica de textos publicitarios en la escuela - Rodríguez Alvarado, Zulma Nayibe (Universidad Antonio Nariño, 2023)
In this research monograph entitled: The truth is not as they paint it sequence didactics to promote the development of critical reading of advertising texts at school, The objective is the development of a pedagogical proposal that allows to favor the critical reading processes, in this case from advertising texts. This research arises from the need to improve the conditions in which the processes of teaching and learning of critical reading, in such a way that teachers can implement strategies that allow them to recognize the different abilities and skills students' readers and also enhance abilities associated with reading and critical thinking. In the first chapter that constitutes the formulation of the problem, a delimitation is made research problem that will be addressed throughout this document and the justification that supports or sustains the approaches that are exposed. Thus, highlighting importance of the use of advertising texts to promote the development of skills related to reading comprehension. In chapter II, the background taking into account some works that served as support for the construction of theoretical foundations, results, and experiences that contributed significantly on the research. In the III chapter the theoretical referents are presented where the investigation and theoretical information of conceptions and theories that constitute the support to this research work In chapter IV the Methodological Design is presented, in which the approach of implementation, qualitative processes aimed at action research through 4 which is oriented the development of the proposal whose perspective is the closest look towards a reality, a natural and daily context, as well as the study of the quality of resources activities and/or tools within a problem situation, in the same way they are detailed verbal as well as non-verbal expressions. Chapter V presents the results obtained and the proposed sequence. didactics based on the analysis of advertising texts taking into account the approach of the promotion of text comprehension and critical culture Given the need that must be assumed from teaching, finally in this work evidenced how pedagogical proposals can be built from the interests of the students, this in order to train students capable of reading critically